'Fundamental causes' of inequalities in mortality: an empirical test of the theory in 20 European populations. Issue 7 (31st March 2017) - Mackenbach, Johan P.; Looman, Caspar W.N.; Artnik, Barbara; Bopp, Matthias; Deboosere, Patrick; Dibben, Chris; Kalediene, Ramune; Kovács, Katalin; Leinsalu, Mall; Martikainen, Pekka; Regidor, Enrique; Rychtaříková, Jitka; et al.
Abstract: The 'fundamental causes' theory stipulates that when new opportunities for lowering mortality arise, higher socioeconomic groups will benefit more because of their greater material and non‐material resources. We tested this theory using harmonised mortality data by educational level for 22 causes of death and 20 European populations from the period 1980–2010. Across all causes and populations, mortality on average declined by 2.49 per cent (95%CI: 2.04–2.92), 1.83% (1.37–2.30) and 1.34% (0.89–1.78) per annum among the high, mid and low educated, respectively. In 69 per cent of cases of declining mortality, mortality declined faster among the high than among the low educated. However, when mortality increased, less increase among the high educated was found in only 46 per cent of cases. Faster mortality decline among the high educated was more manifest for causes of death amenable to intervention than for non‐amenable causes. The difference in mortality decline between education groups was not larger when income inequalities were greater. While our results provide support for the fundamental causes theory, our results suggest that other mechanisms than the theory implies also play a role.